The Patient Satisfaction Level Analysis on the Application of Compliance with Islamic Law Elements in Sultan Agung Islamic Oral and Dental Hospital - Niam, Moh Husnun; Syaharani, Daffa Aulia; Ratnawati, Irma Dewi (Odonto : Dental Journal, 2023)
Background: The existence of hospitals that apply sharia hospital standards can be a solution to muslim communities in Indonesia. Many hospitals currently go by the label of being Islamic hospitals, but their applications have yet to comply with sharia standards. The success of hospital services can be seen in service quality, one can be seen from element of compliance with Islamic law.Method: This study applied analytical observational research (cross-sectional) using an accidental sampling technique of 133 patients. The variables in this study included the independent variable, the application of the element of compliance with Islamic law, while the level of patients' satisfaction served as its dependent variable. Distribution of a questionnaire was used for the instrument. Analysis of the data that has been obtained is then processed using the SPSS Spearman correlation test program. Result: This study used a program using the Spearman correlation test. The study showed a relationship between applying the element of compliance with Islamic law and the level of patients' satisfaction at Rumah Sakit Islam Gigi dan Mulut Pendidikan (RSIGMP) Sultan Agung Semarang (P=0,000). Applying the element of compliance with Islamic law revealed that results averaged 79,9 fell into the range 61-90 being very good and patients' satisfaction yielded an average of 22,5 fell into the range 16,7-25 being very satisfied.Conclusion: The level of patients' satisfaction is related to applying the element of compliance with Islamic law. The better the application of the element of compliance with Islamic law, the better the patients' satisfaction. Applying the compliance with Islamic law and patients’ satisfaction have been performed properly.